Qur’anic Exegesis and Religious Moderation in South Sulawesi: The Law on Blasphemy to Gods of Non-Muslims in Islamic Law Perspective - Mahfudz, Muhsin; Yuspiani, Yuspiani (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
As a country of various ethnicities, languages, and religions, religious moderation is a particularly crucial issue in Indonesia. This paper aimed to elaborate on the law on blasphemy to Gods of non-Islamic religions. The study included a phenomenological qualitative study using the approach of tafsir tahlili (analytical exegesis) and Islamic law. Data were collected by means of in-depth interviews with religious leaders, academicians, and community leaders in South Sulawesi, especially in the cities of Makassar, Barru, and Bone. In addition, literature review was used to refer to books of exegesis, journal articles, and other relevant references. Findings of the study revealed that religious moderation emphasized in the Qur’an is a teaching that promotes tolerant and peaceful relations. Ummatan wasaṭan in the Qur’an could be understood as the people who are always in goodness and justice, show a commendable attitude, and do not easily criticize people nor blame other groups. The opinions of exegetes and field data have also suggested that interpretations of the Qur’an should prioritize a moderate understanding, as conflict might occur due to intolerant attitudes in Indonesia, a country with various religions. Textually understanding the verses of the Qur’an and hadith might also lead to radicalism and even terrorism. In the context of Islamic law, blasphemy towards the Gods of non-Muslims is haram (prohibited) because it may result in others insulting Allah and social conflict; avoiding conflict is a behavior that is in line with the aims of Islamic law (maqāṣid al-sharī'ah). This study thus argues that religious moderation is a crucial attitude, as it can foster tolerance and mutual respect among religious people. Even though other people have different gods from the belief of Muslims, respect for such differences shall exist as directed by the Qur’an.